Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

For $\displaystyle\int_0^{\infty}x^n\frac{\sinh ax}{\cosh bx}\text{d}x$, $\left|a\right|<b$

I think we can evaluate $\displaystyle\int_{0}^{\infty }{{{\text{e}}^{cx}}\frac{\sinh ax}{\cosh bx}\text{d}x}$ first. And use taylor expansion on parameter $c$? But I m not confident on that. Could anyone finish this? : )

share|cite|improve this question
up vote 1 down vote accepted

We already have the solution mentioned here for the integral $$\int_0^{\infty} x^n \dfrac{\sinh(ax)}{\cosh(bx)}dx, \,\,\,\,\,\,\,\, \vert a \vert < b$$

Here is another solution, if you want to proceed by evaluating the integral $$I = \int_0^{\infty} e^{cx} \dfrac{\sinh(ax)}{\cosh(bx)}dx$$ Choose a small enough positive $c$ or choose $c<0$. As in the earlier proof, we have \begin{align} I & = \sum_{k=0}^{\infty} (-1)^k \int_0^{\infty} \left(e^{(a-2kb-b+c)x} - e^{-(a+2kb+b-c)x}\right)dx\\ & = \sum_{k=0}^{\infty} (-1)^k \left(\dfrac1{2kb+b-a-c} - \dfrac1{2kb+b+a-c}\right)\\ & = \sum_{k=0}^{\infty} (-1)^k \left(\dfrac1{2kb+b-a}\left(\sum_{j=0}^{\infty} \left(\dfrac{c}{2kb+b-a} \right)^j\right) - \dfrac1{2kb+b+a} \left(\sum_{j=0}^{\infty} \left(\dfrac{c}{2kb+b+a} \right)^j\right)\right)\\ & = \sum_{j=0}^{\infty} \left(\sum_{k=0}^{\infty} (-1)^k \left(\left(\dfrac1{2kb+b-a} \right)^{j+1} - \left(\dfrac1{2kb+b+a} \right)^{j+1} \right) c^j\right) \end{align} But the integral is also equal to $$I = \int_0^{\infty} e^{cx} \dfrac{\sinh(ax)}{\cosh(bx)} dx = \int_0^{\infty} \sum_{j=0}^{\infty} \dfrac{c^j x^j}{j!} \dfrac{\sinh(ax)}{\cosh(bx)} dx = \sum_{j=0}^{\infty} \left(\int_0^{\infty} \dfrac{x^j}{j!} \dfrac{\sinh(ax)}{\cosh(bx)} dx \right)c^j$$ Now comparing the coefficient of $c^j$, we can now conclude that $$\int_0^{\infty} \dfrac{x^j}{j!} \dfrac{\sinh(ax)}{\cosh(bx)} dx = \sum_{k=0}^{\infty} (-1)^k \left(\left(\dfrac1{2kb+b-a} \right)^{j+1} - \left(\dfrac1{2kb+b+a} \right)^{j+1} \right)$$ Now as before, write $$\tan(\pi x/2) = \dfrac1{\pi} \lim_{N \to \infty}\left(\sum_{k=-N}^N \dfrac2{1-x+2k}\right)$$ Plugging in $x=a/b$ and taking derivative term by term you should be able to obtain your desired result.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.